EFFECTS OF ( Artemisia herba-alba) AND (Urtica dioica) ON SOME BLOOD PARAMETERS IN BROILER CHICK WHICH INFECTED EXPERIMENTALLY WITH Eimeria tenell - Haider M. Ali; Dunya A.M. Mohammad; Amal H. Atyha (Basrah Journal of Veterinary Research)
This study was carried out to determine the effect of the herb and Urtica dioica of the vitality of the Eimeria tenella, it conducted on 150 Ross broiler chicks, divided randomly on the seventh days into six groups. The last two groups (five and six) were considered as a positive and negative control groups, the first five groups were experimentally infected by 1000 oocysts/bird of Eimeria tenella at 17 days old directly in to the crop. The first four groups were given Artemisia herba alba and Urtica dioica According to concentrations for each group. Results were indicated a higher significant differences ( P